Systematic investigation of PRMT6 substrate recognition reveals broad specificity with a preference for an RG motif or basic and bulky residues. (14th April 2021) - Hamey, Joshua J.; Rakow, Sinja; Bouchard, Caroline; Senst, Johanna M.; Kolb, Peter; Bauer, Uta‐Maria; Wilkins, Marc R.; Hart‐Smith, Gene
Abstract : Protein arginine methyltransferase 6 (PRMT6) catalyses the asymmetric dimethylation of arginines on numerous substrate proteins within the human cell. In particular, PRMT6 methylates histone H3 arginine 2 (H3R2) which affects both gene repression and activation. However, the substrate specificity of PRMT6 has not been comprehensively analysed. Here, we systematically characterise the substrate recognition motif of PRMT6, finding that it has broad specificity and recognises the RG motif. Working with a H3 tail peptide as a template, on which we made 204 amino acid substitutions, we use targeted mass spectrometry to measure their effect on PRMT6 in vitro activity. We first show that PRMT6 methylates R2 and R8 in the H3 peptide, although H3R8 is methylated with lower efficiency and is not an in vivo PRMT6 substrate. We then quantify the effect of 194 of these amino acid substitutions on methylation at both H3R2 and H3R8. In both cases, we find that PRMT6 tolerates essentially any amino acid substitution in the H3 peptide, but that positively charged and bulky residues are preferred near the target arginine. We show that PRMT6 also has preference for glycine, but only in the position immediately following the target arginine. This indicates that PRMT6 recognises the RG motif rather than the RGG motif. We further confirm this preference for the RG motif on another PRMT6 substrate, histone H4R3. This broad specificity and recognition of RG rather than RGG are distinctive among the PRMT family and has implications for the development of drugs to selectively target PRMT6. Databases: Panorama Public (https://panoramaweb.org/PRMT6motif.url ); ProteomeXchange (PXD016711). Abstract : Protein arginine methyltransferase 6 (PRMT6) is an important regulator within the human cell, methylating arginine residues in many different proteins to modulate their functions. Here, we show that PRMT6 has broad sequence specificity when methylating its substrates, but prefers basic and bulky residues surrounding the target arginine. We also show that it recognises an arginine–glycine ('RG') motif, rather than the arginine–glycine–glycine ('RGG') motif recognised by other PRMTs.